Voice assimilation of morphemic -s in the L2 English of L1 French, L1 Italian and L1 Spanish learners - Leonardo Contreras Roa; Paolo Mairano; Marc Capliez; Caroline Bouzon (Anglophonia)
This study investigates the progressive voice assimilation rule in word-final morphemic -s in L2 English. We have analyzed data from the IPCE-IPAC corpus of learner oral productions, by measuring periodicity for all learner realizations of morphemic -s. We have compared three groups, namely 15 L1 French learners, 15 L1 Italian learners, and 10 L1 Spanish learners. Given the different distributions and status of [s] and [z] in the participants’ L1s and based on SLM (Speech Learning Model) and MDH (Markedness Differential Hypothesis), we hypothesized that L1 French learners and L1 Italian learners would find it easier than L1 Spanish learners to reproduce the outcome of the voice assimilation rule, but our predictions are only partially confirmed by the results: L1 French learners (who have /s/ and /z/ in their L1 as phonemes occurring in word-final position) are indeed the most successful in producing the expected patterns of periodicity. However, L1 Spanish learners outperform L1 Italian learners in producing periodicity in voiced contexts. We compare these results with our previous analysis of voicing for non-morphemic /s/ and /z/ by the same speakers, and we discuss our findings in relation to the markedness of these two sounds. We propose that the /s/ ~ /z/ voicing opposition may constitute an exception to the markedness hierarchy of voice contrasts for obstruents (word-initial < word-medial < word-final), whereby the word-final position is not more marked than the other positions. Additionally, if taken together, the results of this and our previous study reveal differences in the voicing of morphemic vs non-morphemic realizations for sibilants in L2 English (similar to L1 English). This may have repercussions on models of L2 phonology acquisition, which do not presently take into account an interaction between L2 sounds and their morphemic status.